Profil Bakteri dari Usap Tenggorok Penderita Infeksi Saluran Pernapasan Usia Sekolah Dasar di Puskesmas Tamalanrea Makassar - Nomarihi Goraahe; Nadyah Haruna; Najamuddin Najamuddin; Andi Irhamnia Sakinah; Arifuddin Ahmad (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Acute respiratory infection (ARI) is a condition that occurs in one or more areas of the human respiratory tract and is associated with the environmental conditions in which the patient resides. The most frequent cause of ARI is infection with Streptococcus pneumonia or Haemophilus influenza. In order to diagnose ARI by identifying the infectious agent responsible for its development, laboratory tests can be conducted on throat swab samples from patient who exhibit symptoms of ARI.. One of the objectives of this investigation was to ascertain the bacterial profile of children with ARI. This study is a descriptive cross-sectional investigation that utilised specimens from throat swabs of ARI patients in elementary school-age children who visited the Tamalanrea Makassar Health Centre between October 10, 2022, and November 10, 2022. The biopsy results were subsequently subjected to gramme staining and identification tests to ascertain the species of causative bacteria. In the 57 children, which consisted of 38 boys and 19 girls, the percentage of monobacterial findings was 49 (85.96%) and 8 (14.04) polymicrobial. Gram-positive bacteria were found 50.8% and gram-negative bacteria 49.2%, with Staphylococcus aureus being the most common cause.